Pelatihan pengolahan ikan dan pengemasan produk pertanian untuk pengembangan industri hilir desa Labuh Air Pandan - Reniati Reniati; Sumiyati Sumiyati; Muhammad Faisal Akbar (ABSYARA: Jurnal Pengabdian Pada Masayarakat, 2021)
The agricultural, forestry, and fishery sectors in Bangka Belitung are the second largest contributor to gross regional domestic product (GRDP). At the same time, the manufacturing industry is the sector with the most significant contribution to GRDP. However, Labuh Air Pandan Village is not recorded as a contributor to local revenue, even though this village has the most significant agricultural land compared to other villages because the village products have not competed with other local products. After all, so far, they have been packaged in conventional forms. In addition, as an area directly adjacent to the Bangka Strait, this village has quite a lot of potential for marine products. However, the marine products obtained are only sold in raw commodities without further processing, such as finished products. This activity aims to provide socialization regarding fish processing and product packaging for farmer and fisherman groups in Labuhan Air Pandan Village. The method of this service activity is educative and demonstration by conducting socialization of making fish sauce and socializing product packaging. This activity lasted for one month in Labuh Air Pandan Village. Evaluation is done by providing feedback in the form of a list of questions related to understanding and interest in this activity. Based on the results of the evaluation, it was found that 80% of participants stated that they understood what was conveyed from the socialization of fishery product processing and agricultural product packaging